The role of the sixth component of complement in the rejection of kidney xenografts - Mejía-Laguna, J. E. (1970)
The time of rejection of dog kidney grafts in normal and in C6-deficient rabbits was not significantly different. It is concluded that the last four components of complement are not involved in this form of violent xenograft rejection. The requirement for the first components may be explained by polymorphonuclear leucocyte chemotaxis, since these cells were found in the glomeruli of rejected kidneys.